DENSITY OF Escherichia coli BACTERIA AND HETEROTROPHIC BACTERIA IN DUMAI SEAWATER OF RIAUPROVINCE - Anisa Qoriman; Feliatra Feliatra; Nursyirwani Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted from April until May 2018. The purpose of this study was to calculate the density of Escherichia coli in sea water of Dumai, to determine the ratio of E. coli to heterotrophic bacteria and to examine the resistance of E. coli to antibiotics. In this study the determination of sampling points using purposive sampling method, was set intothree sampling points for each station. Density ofE.coliwas calculated by using the Most Probable Number (MPN) method and density total of heterotrophic bacteria by using spread plate count method. The result showed that densityE. colirangedfrom 2.37 x 104 – 1.1 x 105 CFU/ml. The highest MPN number ofE. coliwas found in stations 2 and 3, andthe lowest wasin station 5. The total number of heterotrophic bacteria ranged from 7.37 x 106 – 10.38 x 106 CFU/ml. The highest number of heterotrophic was foundin station 4 and the lowest was in station 5.The highest percentage ratio of density of E.colito heterotrophic bacteriawas in station 2(1.20%)and the lowest was in station 5 (0.32%).Resistance of E.coli toward chloramphenicol as antibiotic testedindicated that 7 isolateswere resistant with the inhibition zone ranged from 2.17 –10.70 mm, 9 isolates were categorized intointermediate with the inhibition zone ranged from 11.90–19.33 mm and 1 isolate was sensitive with the inhibition zone was 22.77 mm. Towardantibiotics penicillin andisoniazid, all bacterial isolates were resistant with the inhibition zone ranged from 0.80 - 4.70 mm and 1.50- 4.67 mm, respectively.Keyword: Density, Escherichia coli,MPN method, Heterotrophic Bacteria, Antibiotics